The Relationship between ELISA and HI Tests for Determination the Antibodies of Rubbela: Layla Fouad Ali and Ghanima Sadik M. - Ali, Layla Fouad (The Iraqi Journal of Veterinary Medicine, 2012)
The study includes (44) blood samples were vaccinated with MMR vaccine. The IgM antibodies of Rubbela Virus were measured by HI test, 22 samples were positive and 22 were negative. These samples were tested by Enzyme Linked Immuno Sorbant Assay ELISA test to determine the relationship between them. The results showed that ELISA test was more sensitivities than Haemagglutination inhibition HI test in determination of rubella specific antibodies, so it is better than HI test in measuring the immune-status of individuals vaccinated with rubella vaccine and there was a positive relationship between ELISA test and HI test and was detected (r= 0.585).